2016
DOI: 10.2147/ptt.s85194
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis and inflammatory bowel disease: links and risks

Abstract: Psoriasis and the spectrum of inflammatory bowel diseases (IBD) are chronic, inflammatory, organotropic conditions. The epidemiologic coexistence of these diseases is corroborated by findings at the level of disease, biogeography, and intrafamilial and intrapatient coincidence. The identification of shared susceptibility loci and DNA polymorphisms has confirmed this correlation at a genetic level. The pathogenesis of both diseases implicates the innate and adaptive segments of the immune system. Increased perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 242 publications
(175 reference statements)
0
18
0
Order By: Relevance
“…Previous studies revealed that psoriasis and IBD have highly overlapping epidemiological characteristics, genetic susceptibility loci, disease risk factors, immune mechanisms, and comorbidities. IBD patients and psoriasis patients have increased probability of suffering from the other disease [ 1 , 2 ]. Although some clinical cases about the use of interleukin (IL)-17 blockers inducing CD have been reported, the patient had suffered from psoriasis and CD before the use of IL-17 inhibitor is quite rare.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies revealed that psoriasis and IBD have highly overlapping epidemiological characteristics, genetic susceptibility loci, disease risk factors, immune mechanisms, and comorbidities. IBD patients and psoriasis patients have increased probability of suffering from the other disease [ 1 , 2 ]. Although some clinical cases about the use of interleukin (IL)-17 blockers inducing CD have been reported, the patient had suffered from psoriasis and CD before the use of IL-17 inhibitor is quite rare.…”
Section: Introductionmentioning
confidence: 99%
“…Based on our studies, colonization of the gastrointestinal tract of germ-free (GF) animals with one bacterial strain or complex intestinal microbiota influences the host immune system at the local and systemic level, promoting proinflammatory or anti-inflammatory response, depending on the species used (Tlaskalova-Hogenova et al., 2011). The importance of the gut-skin axis in pathogenesis of psoriasis has been recently documented in humans as well as in animal models of psoriasis (Fry et al., 2013; Zanvit et al., 2015; Vlachos et al., 2016; Zakostelska et al., 2016; Drago et al., 2018). Recovery from intestinal dysbiosis, e.g., by healing the syndrome of small intestinal bacterial overgrowth, may mitigate the symptoms of psoriatic patients (Drago et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The anatomical and functional integrity of the tissue environment barriers is compromised in the skin of psoriasis patients and intestinal lumen of IBD patients. 3 Psoriasis and IBD are linked epidemiologically as well as genetically. In a population-based nationwide study in Korea, psoriasis patients had a higher risk of IBD than did the general population.…”
Section: Discussionmentioning
confidence: 99%